Exploring professional work-ready graduate attributes from the employer perspective - Rufai, Ahmed Umar; Bakar, Ab. Rahim; Mat Rashid, Abdullah (Contemporary Research Center, 2015)
Purpose - The purpose of this paper is to explore what we mean by professional work-ready graduate attributes from the employer perspective. Design/ Methodology/ Approach - The research design was essentially qualitative. Following, Yin’s (2003) suggestion, the researcher gathered data through three primary sources, namely, document, conducted semi-structured interviews and recorded observations, at three large multinational companies. The researcher analyzed and interpreted the data collected in form of field notes, interview scripts, audio recording and information from documents. Yorke and Knight, (2004), emergent work of skills research initiative known as USEM account of employability was integrated as conceptual frameworks. Findings - Three themes emerged, the findings highlighted three broad areas considered to constitute, what employers described as graduate attributes, this includes soft skills/personal attributes; subject specific skills and disciplinary content knowledge and understanding. Research/Limitation/Implication - Collective voice of employers on acceptable meaning of what graduate attribute stands for, will lead to establishing a common higher education programme or curricula that is work-based and skill oriented, which in turn help students to develop broad range of skills, work attitudes and values to face future challenges of the world competitive market. Original value - This paper seek to fill the ‘skill gap’ occurring between the demand and the level of educational preparation of graduates, by providing acceptable meaning of work-ready graduate attributes.